Long noncoding RNA TARID directs demethylation and activation of the tumor suppressor TCF21 via GADD45A - Arab, Khelifa; Park, Yoon Jung; Lindroth, Anders M.; Schäfer, Andrea; Oakes, Christopher; Weichenhan, Dieter; Lukanova, Annekatrin; Lundin, Eva; Risch, Angela; Meister, Michael; Dienemann, Hendrik; Dyckhoff, Gerhard; et al. (Molecular cell, 2014)
DNA methylation is a dynamic and reversible process that governs gene expression during development and disease. Several examples of active DNA demethylation have been documented, involving genome-wide and gene-specific DNA demethylation. How demethylating enzymes are targeted to specific genomic loci remains largely unknown. We show that an antisense lncRNA, termed TARID (for TCF21 antisense RNA inducing demethylation), activates TCF21 expression by inducing promoter demethylation. TARID interacts with both the TCF21 promoter and GADD45A (growth arrest and DNA-damage-inducible, alpha), a regulator of DNA demethylation. GADD45A in turn recruits thymine-DNA glycosylase for base excision repair-mediated demethylation involving oxidation of 5-methylcytosine to 5-hydroxymethylcytosine in the TCF21 promoter by ten-eleven translocation methylcytosine dioxygenase proteins. The results reveal a function of lncRNAs, serving as a genomic address label for GADD45A-mediated demethylation of specific target genes.